The effect of surface modification of (micro/nano)-calcium carbonate particles at various ratios on mechanical properties of poly(vinyl chloride) composites. (April 2015) - Jazi, Seyyd Hamid Sajjadi; Bagheri, Ruhollah; Esfahany, Mohsen Nasr
The surface of micro and nanoparticles of calcium carbonate (CaCO3 ) was modified by 3-mercaptopropyl trimethoxysilane and polymethylhydrogensiloxane. Fourier transform infrared spectra of extracted CaCO3 particles revealed interfacial bonding between coupling agents and CaCO3 particles. Poly(vinyl chloride) (PVC)/surface-modified CaCO3 with different mass ratios of (micro/nano)-CaCO3 particles were melt blended using a Brabender torque rheometer and kept with a constant content of CaCO3 . The impact strength, tensile strength, elongation at break, and Young's modulus of the composites were considerably enhanced at 9/6 mass ratio of (micro/nano)-CaCO3 . The mechanical properties were improved relative to the pure PVC due to the interfacial bonding between the filler and the matrix. Scanning electron microscopic images of fractured surfaces of the test specimens showed larger voids with nonsmooth edge around the cavities, as compared with the nano-CaCO3 /PVC composite, which is more pronounced by the increase in the micro particles contents.